Zerumbone: a potent emerging phytochemical with anticancer therapeutic potential - Ahmad Jamil, Nur Aqilah Huda; Hoongli, Sylvia Chong; Abdullah, Nurul Akmaryanti; Mohamad Zakuan, Noraina; Abdul Hamid, Hafizah; Mehat, Muhammad Zulfadli; Cheema, Manraj Singh; Md Hashim, Nur Fariesha (Penerbit Universiti Kebangsaan Malaysia (UKM Press), 2023)
Breast cancer is a prevalent cause of global mortality, characterised by abnormal cell growth within the breast. These cells can spread to distant sites in the body through metastasis and one of the mechanisms that breast cancer cells use to metastasise is via invadopodia formation. Accumulated evidences have explained pathways that may contribute to the breast cancer cells metastasis including the ERK, SMAD-3, STAT3 and NF-ºB pathways. The hypoxic conditions within tumours enhance their metastatic ability through HIF-1± upregulation. Despite advanced treatments including chemotherapy and radiotherapy, these approaches are expensive and sometimes lack efficacy. Zerumbone, a compound extracted from Zingiber zerumbet, is known for its anti-cancer properties. It counteracts cancer cell metastasis by reducing cell migration, invasion and proliferation by acting upon multiple signalling pathways. This review recapitulates the metastasis of breast cancer and its biomarkers. In addition, our review also will explore the impact of zerumbone, therapeutic roles and its mechanism of action in reducing breast cancer metastasis.